Dynamics of NKT-Cell Responses to Chlamydial Infection - Shekhar, Sudhanshu; Joyee, Antony George; Yang, Xi (Frontiers in Immunology, 2015)
Natural killer T (NKT) cells have gained great attention owing to their critical functional roles in immunity to various pathogens. In this review, we provide an overview of the current knowledge on the role of NKT cells in host defense against and pathogenesis due to Chlamydia, which is an intracellular bacterial pathogen that poses a threat to the public health worldwide. Accumulating evidence has demonstrated that NKT cells, particularly invariant NKT (iNKT) cells, play a crucial role in host defense against chlamydial infections, especially in C. pneumoniae infection. iNKT cells can promote type-1 protective responses to C. pneumoniae by inducing enhanced production of IL-12 by dendritic cells (DCs), in particular CD8α+ DCs, which promote the differentiation of naive T cells into protective IFN-γ-producing Th1/Tc1 type CD4+/CD8+ T cells. This iNKT-cell-mediated modulation of DC function is largely dependent upon CD40-CD40L interaction, IFN-γ production and cell-to-cell contact. In addition, iNKT cells modulate the function of NK cells. NKT cells may be also involved in the pathogenesis of some chlamydial diseases by inducing different patterns of cytokine production. A better understanding of NKT-cell biology will enable us to rationally design prophylactic and therapeutic tools to combat infectious diseases.